The last post: British press representations of veterans of the Great War. (December 2014) - Webber, Nick; Long, Paul
Harry Patch (1898–2009) was the last surviving soldier to have fought in the trenches of the Western Front, entering the media spotlight in 1998 when he was approached to contribute to the BBC documentary Veterans . Media coverage of Patch and the cultivation of his totemic status were particularly prodigious in anticipating and marking his death, producing a range of reflections on its historical, social and cultural significance. Focusing on the British popular press, this article examines media coverage of the last decade of Patch's life. It considers the way in which the Great War is memorialised in the space of public history of the media in terms of the personalisation and sentimentalisation of Patch, exploring how he serves as a synecdoche for the millions of others who fought, how he embodies ideas of generational and social change, and how the iconography of the Great War's contemporaneous representation works in the space of its memorialisation.